One independent or many independent? The relationship among self-construal, number of brand endorsers, and brand attitudes - Liang, Shichang; Cai, Kunhan; Zhang, Yiwei; Yuan, Xueying; Pan, Siyu; Teng, Lili (Frontiers in Psychology, 2024)
It was common for brands to use different numbers of endorsers in marketing practice. Nevertheless, research on brand endorsers' quantity has not yielded a uniform consensus. The previous research about brand endorsers mainly focuses on the appeal of endorsement, brand category, and endorser characteristics, paying less attention to the impact of cultural factors, particularly self-construal. This study delves into selecting brand endorsers across diverse cultural regions for the same brand. Drawing on the principles of self-consistency theory and self-construal theory, our research, conducted through three distinct experiments, reveals that consumers tend to hold more favorable opinions about brands endorsed by a single individual. Furthermore, self-consistency emerges as a crucial mediating factor in this phenomenon. Additionally, self-construal is an essential factor among consumers from various cultural backgrounds. Consumers with an independent self-construal exhibit more favorable brand perceptions when it comes to single-endorser brands compared to their counterparts with an interdependent self-construal. Conversely, individuals with an interdependent self-construal demonstrate a more positive disposition towards brands with multiple endorsers than those with an independent self-construal. This research not only enriches and extends our theoretical understanding of the impact of the number of brand endorsers on consumer brand attitudes but also provides valuable practical insights for optimizing the selection of brand endorsers for companies.